IPTEKS KETEPATWAKTUAN DAN KETERANDALAN PELAPORAN KEUANGAN DITINJAU DARI PENGENDALIAN INTERNAL PADA BADAN KEUANGAN DAERAH KOTA TOMOHON - Langkedeng, Don Juan Jacobs; Saerang, David P. E. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Accounting information systems and controls adequate internal can provide complete conclusions from a information conditions in the government to be used as accounting information for determine accuracy input data to output to be used government decision making. The research is entitled Effect of Technology Information and Understanding of Auditors on Internal Control of the Process Information System Audit (Survey on BKD Tomohon City). Purpose of research form knowing the effect of information technology on the information system audit process , m know the influence of the auditor's understanding of internal control over information system audit process and form know the influence of information technology, the auditor's management of internal control of the system audit process information on the Tomohon City Regional Finance Agency. Method research uses explanatory methods with data collection techniques through observation, questionnaire. Research results shows that information technology at the Agency Regional Finance of Tomohon City has a strong and significant to the audit process it information system. Technology information can help and facilitate the auditor in carrying out the system audit process information. The auditor's understanding of internal control of the Agency Regional Finance of Tomohon City has a moderate and significant relationship with the information system audit process. The information system audit process is running well and produce a good report if the auditor is capable understand the internal control system well, especially control internal with the presence of computerization. Information Technology and control internal has a strong and significant influence on the audit process information at the Regional Finance Agency of Tomohon City. Use of technology better information and auditor understanding of internal controllable to improve and facilitate the information system audit process. Information technology improvement auditor's assessment and assessment of internal controllable to improve the information system audit process even better. Decline information technology and understanding of capable internal controls reduce the efficiency and effectiveness of the information system audit process information.Keywords: Internal Informasion On The Timelty And Reability Of Financial Reporting